Determination of Nitinol Fibers Performances by Means of Embedded Systems - Kadir SABANCI; Murat KOKLU; Serafettin EKINCI (International Journal of Applied Methods in Electronics and Computers, 2015)
Utilization of shape memory alloys is rapidly spreading to many technological areas. From this point, alloys with shape memory are used in various fields such as temperature sensors in electronics, test valves in medicine, radiator fans in automotive and multi leg mobile robots. Application of nitinol fibers, which are actually shape memory alloys, as muscle fibers in industrial robots are increasing day by day. In this study, several tests were carried on aiming for the operational performance of nitinol fibers that are easy to control, economic, silent and harmless to environment and that have increasing utilization in recent motion technology. By using embedded systems, contraction (spasm) ratios and electrical current passing through the fibers were measured after 0.04 and 0.06 inch nitinol fibers were subjected to various voltages. Additionally, yielding limit value of  system in the Open Source Arduino Mega electronic card.